2009
DOI: 10.1590/s1806-83242009000300019
|View full text |Cite
|
Sign up to set email alerts
|

Influence of chlorhexidine concentration on microtensile bond strength of contemporary adhesive systems

Abstract: The purpose of this study was to investigate the influence of chlorhexidine (CHX) concentration on the microtensile bond strength (muTBS) of contemporary adhesive systems. Eighty bovine central incisors were used in this study. The facial enamel surface of the crowns was abraded with 600-grit silicon carbide paper to expose flat, mid-coronal dentin surfaces. The tested materials were Scotchbond Multipurpose (SMP), Single-Bond (SB), Clearfil SE Bond (CSEB) and Clearfil Tri S Bond (CTSB). All the materials were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
2
10

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 13 publications
2
53
2
10
Order By: Relevance
“…Nevertheless, these results do not agree with earlier reports showing decreased bond strengths when self-etch adhesive systems were applied after CHXbased cavity disinfectant. 7,8,10 This divergence may be due to the different adhesive tested in the earlier studies (two-step self-etch Clearfill SE Bond), which has a composition different from that of the twocomponent all-in-one self-etch All-Bond SE, thus interacting differently with CHX and the smear layer. Our data also diverge from those of another study, which demonstrated increased bond strength of a self-etch adhesive system after carious dentin was treated with a 5% CHX solution.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, these results do not agree with earlier reports showing decreased bond strengths when self-etch adhesive systems were applied after CHXbased cavity disinfectant. 7,8,10 This divergence may be due to the different adhesive tested in the earlier studies (two-step self-etch Clearfill SE Bond), which has a composition different from that of the twocomponent all-in-one self-etch All-Bond SE, thus interacting differently with CHX and the smear layer. Our data also diverge from those of another study, which demonstrated increased bond strength of a self-etch adhesive system after carious dentin was treated with a 5% CHX solution.…”
Section: Discussionmentioning
confidence: 99%
“…The remineralizing solution contained 1.5 mM of calcium (CaCl 2 ), 0.9 mM of phosphate (KH 2 PO 4 ), sticks with a cross-sectional area of approximately 0.8 mm², measured with a digital caliper. 11 Each stick was glued with cyanoacrylate-based adhesive (Zapit Base and Accelerator, Dental Ventures of America Inc., Corona, USA), attached to opposing arms of the testing device and finally stressed until failure with a tensile force in a microtensile testing machine 8 (Micro Tensile Tester, T-61010 K, Bisco, Schaumburg, USA) at a crosshead speed of 1 mm/ minute. The bond strength (MPa) of each specimen was determined as the failure load (N) divided by the cross-sectional area of the bonded interface.…”
Section: Ph-cyclingmentioning
confidence: 99%
See 1 more Smart Citation
“…74,85,86,87 The use of 2% CHX solution as an effective and nonspecific protease inhibitor primer, after acid-etching, is attractive from a clinical point of view, since it is already used in other oral health situations as an antimicrobial agent. 88 Compared to control, aged CHX-treated dentin relates to higher bond strength values 73,74,77,78,79,80,89,90,91,92 which are interestingly equivalent to each other in most of the immediate evaluations. 93 Especially when two step etch-and-rinse adhesives are used, reduction of bond strength values for conventionally treated dentin over one to two years is of approximately 50%; when CHX is applied after acid etching, total reduction is around 20% 72 to 84.9%.…”
Section: Enzymatic Inhibitorsmentioning
confidence: 92%
“…73 Regarding the effectiveness of self-etch adhesives, and even the moment or how CHX must be applied, are conflicting. 74,90,117,118,119 Recent systematic reviews show that an aging-associated decline in dentin bond strength of both categories of adhesives can be lessened by CHX application. 74,118,119 In this sense, a growing predisposition among clinicians in properly applying 0.2-2% CHX for 15-60 s for re-wetting the collagen network on acid-etched dentin 77,79,89,120 to minimize degradation of resin-dentin bonds, can be currently appreciated.…”
Section: Enzymatic Inhibitorsmentioning
confidence: 99%